Modelling of Ballistic Impact over a Ceramic-Metal Protection System - Leandro Neckel; Dachamir Hotza; Daniel Stainer; Rolf Janssen; Hazim Ali Al-Qureshi (Advances in Materials Science and Engineering)
The behavior of ceramic-metal protection against a projectile impact is modeled. The model takes into account the mass and velocity for each stage of the phenomenon. A former model was modified considering more realistic parameters such as geometries and deformation profile. To analyze the model, simulations on different parameters have been run. The impact results of different ballistic projectiles were simulated, and the movement was plotted. In addition, a deterministic simulation on the mechanical properties of the back metal plate properties was done.